SUNSHINE POLICY : KEBUNTUAN CONFIDENCE BUILDING MEASURES SEMENANJUNG KOREA PADA MASA KIM DAEJUNG- ROH MOOHYUN - Bayu Eko Yulianto (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
This paper describes the ineffectiveness of South Korea’s confidence-building measures towards North Korea during the reign of Kim Dae Jung and Roh Moo Hyun through the sunshine policy. The previous studies on the sunshine policy only discussed the efforts made by the South Korean government through the sunshine policy and America's influence on the implementation in general. The studies are divided into three major categories namely: domestic politics, political economy, and regional studies, but none has discussed the causes of the ineffectiveness of the sunshine policy. By using confidence-building measures as an analytical framework, this paper will explain the variables in confidence-building measures that cause sunshine policies to be ineffective. The main argument of this paper is that there are 2 factors that cause the sunshine policy to be ineffective, namely the influence of America and the absence of political will from North Korea to achieve the goal of confidence-building measures through sunshine policy.